Research and conservation priorities to protect wildlife from collisions with vehicles. (April 2023) - Medrano-Vizcaíno, Pablo; Grilo, Clara; González-Suárez, Manuela
Abstract: The rapidly expanding global road network poses threats to wildlife, including direct mortality. Given limited knowledge and resources, strategic allocation is critical. We introduce a method to identify areas and taxa affected by vehicle collisions as priorities to study and protect. The method is illustrated using Latin America as a case study. In this region high biodiversity and an expanding road network can result in high impacts from roads, yet emerging research expertise offers opportunities for action. To identify priority targets, we combined predicted spatially-explicit roadkill rates for birds and mammals with information about the current road network and species conservation status. Priority areas for conservation (with many species susceptible to roadkill but few or inexistent roads) were largely concentrated in the Amazon, while priority areas for research (unstudied regions with many roads and many species susceptible to roadkill) occur in various areas from Southern Mexico to Chile. Priority taxa for conservation reflected studied, roadkill-susceptible groups (e.g., vultures and armadillos), while priority taxa for research were defined as either poorly-studied roadkill-susceptible groups or unstudied groups of conservation concern (e.g., cuckoos and shrew opossums). Our approach offers a tool that could be applied to other areas and taxa to facilitate a more strategic allocation of resources in conservation and research in road ecology. Highlights: Roadkill data and traits define areas and species for protection and research. Future road developments in the Amazon could be devastating for biodiversity. Research on road impacts are urgently needed in Central America and northern South America. Vultures, armadillos, cuckoos and shrew opossums need more protection and research. Our new framework can guide the allocation of resources for conservation and research.